2022
DOI: 10.1177/09612033211067984
|View full text |Cite
|
Sign up to set email alerts
|

A tissue-selective estrogen complex as treatment of osteoporosis in experimental lupus

Abstract: Osteoporosis is a common secondary complication in patients with systemic lupus erythematosus (SLE). Current osteoporosis treatment with bisphosphonates has some negative side effects and there is a lack of data regarding newer treatments options for SLE associated osteoporosis. The tissue-selective estrogen complex (TSEC) containing conjugated estrogens and the selective estrogen receptor modulator bazedoxifene (Bza) is approved for treatment of postmenopausal vasomotor symptoms and prevention of osteoporosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…However, bazedoxifene displays an estrogen agonistic effect by reducing thymic and gonadal fat weight. In line with previous studies, both in immune-induced and naïve ovariectomized mice [ 9 , 10 , 23 ], we demonstrated that estrogen and bazedoxifene have a stimulatory effect on tibial cortical bone compared with vehicle-treated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, bazedoxifene displays an estrogen agonistic effect by reducing thymic and gonadal fat weight. In line with previous studies, both in immune-induced and naïve ovariectomized mice [ 9 , 10 , 23 ], we demonstrated that estrogen and bazedoxifene have a stimulatory effect on tibial cortical bone compared with vehicle-treated.…”
Section: Discussionsupporting
confidence: 92%
“…injected with 17β-estradiol-3-benzoate (E2; 1 μg/mouse/day; Sigma-Aldrich), Bazedoxifene (BZA; 24 μg/mouse/day; Pfizer) dissolved in 100 μl of Miglyol oil or vehicle (100 μl/mice/day; Miglyol oil) 5 times per week for a total of 4 weeks. Treatment doses for E2 and BZA were based on previous findings from our group, which include both healthy ovariectomized C57Bl6 mice [ 11 , 22 ] and in pathogenic conditions such as collagen-induced arthritis a model of RA [ 10 ], and in experimental lupus [ 23 ]. In addition, the body surface is calculated to ensure the dose of BZA used in mice is comparable to doses used in the relevant to human [ 24 ].…”
Section: Methodsmentioning
confidence: 99%